Legal Analysis of Islamic Economic Law on Hybrid Contracts in Islamic Financial Institution Products - Anita Niffilayani; Le thi thao (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This article is intended to philosophically analyze the existence of hybrid contracts or al-’uqûd al-murakkabah (complex contracts) or multi-contracts. The research focuses on the opinions of hadith scholars and fiqh muamalah (Islamic commercial jurisprudence), as well as their applications in Islamic financial institutions. This is crucial because a single contract form cannot adequately respond to the current financial conditions. Transactions are always dynamic and influenced by the financial industry at national, regional, and international levels. This research is a qualitative-literature study with a philosophical-normative approach. It analyzes the hadith texts and scholars' views philosophically, then juxtaposes the ideal-philosophical aspect with the reality in Islamic banking. The study concludes that, first, the Sharia economic law analysis of hadith related to the hybrid contract model explains the prohibition of bai’ataini fi bai’atin (two sales and purchases in one), the prohibition of shafqataini fi shafqatin (two agreements in one), and the prohibition of bay' and salaf (sales agreement and advance payment for goods). Second, the construction of the hybrid model in Islamic banking aims to develop al-’uqûd al-mutaqâbilah (conditional contracts) and al-’uqûd al-Mujtami’ah (similar contracts), implemented in housing financing.